The modern paradigm of pathophysiology, prevention and treatment of heart failure in type 2 diabetes mellitus - Zh. D. Kobalava; V. V. Medovchshikov; N. B. Yeshniyazov; E. R. Khasanova (Российский кардиологический журнал)
Prevention and choice  of therapeutic strategies in patient,s  with type 2 diabetes (T2D) and heart failure (HF) is an urgent problem. This review presents a modern concept for HF development  from early  stages of T2D. Glucose-lowering  and cardiac  medications  for the  prevention  and  treatment of HF depending   on  its phenotypes were considered.